Kontruksi Epistemologi Hukum Islam: Telaah Komprehensif Atas Dalil Al-Qur’an Sebagai Sumber Hukum Dari Aspek Definisi, Kehujjahan, Klasifikasi Qath’i-Zhanni, Karakteristik Bayan Dan Konsekuensi Pengingkarannya - Dina Maharani; Dewi Permata Kusumaningati (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
This research aims to conduct a comprehensive review of the construction of Islamic legal epistemology (ushul fiqh) by positioning the Qur'an as the primary source of law. This study focuses on five fundamental aspects that form the authority and methodology of legal interpretation sourced from the Qur'an. First, the definitional aspect which examines the essence of the Qur'an as a revelation from Allah SWT both linguistically and terminologically. Second, the aspect of authority (hujjiyah) which proves the position of the Qur'an as an absolute, definite, and undoubtedly valid source of law (qath'i al-tsubut). Third, an analysis of the classification of its legal content into qath'i (definite) and zhanni (interpretative) verses from the perspective of textual indication (dalalah), which forms the basis for the dynamics of ijtihad. Fourth, an exploration of the characteristics of the Qur'an's legal explanation method (bayan), which includes forms such as bayan al-taqrir, bayan al-tafsir, bayan al-tasyri', and bayan al-tabdil. Lastly, this study examines the theological and juridical consequences for those who deny the authority of the Qur'an as a source of law, which has implications for their faith status and punishment. The research method used is qualitative with a library research approach that analyzes primary texts of ushul fiqh and tafsir. The conclusion of this study confirms that the Qur'an is not only an authentic source of law, but also has a clear, systematic, and hierarchical epistemological structure, which allows it to be an eternal (shalih li kulli zaman wa makan) and dynamic legal guide through the mechanism of ijtihad in the zhanni verses.